Amyloid Plaques Disrupt Resting State Default Mode Network Connectivity in Cognitively Normal Elderly - Sheline, Yvette I.; Raichle, Marcus E.; Snyder, Abraham Z.; Morris, John C.; Head, Denise; Wang, Suzhi; Mintun, Mark A. (Biological psychiatry (1969), 2010)
Important functional connections within the default mode network (DMN) are disrupted in Alzheimer's disease (AD), likely from amyloid-beta (Aβ) plaque-associated neuronal toxicity. Here, we sought to determine if pathological effects of Aβ amyloid plaques could be seen, even in the absence of a task, by examining functional connectivity in cognitively normal participants with and without preclinical amyloid deposition. Participants with Alzheimer's disease (AD) ( n = 35) were compared with 68 cognitively normal participants who were further subdivided by positron emission tomography (PET) Pittsburgh Compound-B (PIB) imaging into those without evidence of brain amyloid (PIB−) and those with brain amyloid (PIB+) deposition. Resting state functional magnetic resonance imaging (fMRI) demonstrated that, compared with the PIB− group, the PIB+ group differed significantly in functional connectivity of the precuneus to hippocampus, parahippocampus, anterior cingulate, dorsal cingulate, gyrus rectus, superior precuneus, and visual cortex. These differences were in the same regions and in the same direction as differences found in the AD group. Thus, before any manifestations of cognitive or behavioral changes, there were differences in resting state connectivity in cognitively normal subjects with brain amyloid deposition, suggesting that early manifestation of Aβ toxicity can be detected using resting state fMRI.